Variations in bioavailability of dissolved organic matter during a spring flood episode in northern Sweden - Eriksson, Tobias (2004)
This study of spring flood episodes was performed within the catchment of Krycklan, in Svartberget, northern Sweden. The purpose was to better understand changes in total organic carbon (TOC) concentrations and the bioavailability of dissolved organic matter (DOM) during the spring flood and how they differ between stream sites, ranging in size and characteristics. DOM bioavailability was estimated from CO2 production rates (PrRs) and total CO2 production (TPrs), derived by applying standardized bacterial bioassays during approximately 90 days. TOC concentrations in most of the forested streams increased during spring flood. Furthermore, the PrRs per unit of TOC increased by up to 95% when comparing discharge before and after spring flood. These patterns can be explained by the activation of new superficial flow paths in the riparian zone, increasing not only the DOM concentration per se, but also its susceptibility to biological degradation. At a mire-influenced headwater stream, TOC concentrations decreased during peak flow and no differences in DOM bioavailability per unit TOC was observed before and during spring flood. This suggests that the hydrological flow paths in the mire are superficial during most of the year and do not provide any new sources of DOM to the stream during spring flood. Instead, existing sources are diluted due to higher discharge. PrRs and TPrs ranged from 0.10% to 0.43 % of total C pool per day and from 6% to 20% of total C pool over 80 days, respectively. PrRs and TPrs were low in headwaters and increased further downstream. This downstream change was observed during all three bioassays, but was largest before and during spring flood. PrRs were up to four times higher in the outlet of the catchment of Krycklan than in the forest and mire headwaters. The residence time of water in streams within the catchment is small and water temperatures during spring flood are low. Therefore, it is likely that most of the bioavailable DOM will be utilized outside the catchment of Krycklan and ...